Cultural considerations for the second language writing anxiety inventory: Saudi Arabian female university students - Waked, Arifi N.; El-Moussa, Omar; Pilotti, Maura A. E.; Al-Mulhem, Huda; El Alaoui, Khadija; Ahmed, Reem (Frontiers in Education, 2024)
This study examines the applicability of the Second Language Writing Anxiety Inventory (SLWAI) to a population of 857 native Arabic-speaking Saudi Arabian female university students learning English as a foreign language (EFL). Participants were divided into two groups. The first of these consisted of 430 students who participated in the testing portion of the study. The second group consisted of 427 students who participated in the replication portion of this study. SLWAI is typically used to assess the degree of EFL writing anxiety across three dimensions: somatic anxiety, avoidance behavior, and cognitive anxiety. However, factor analysis of the data collected from both groups revealed that these dimensions are not entirely pertinent to the population studied. The three dimensions that emerged are somatic anxiety and two distinct aspects of cognitive anxiety: proficiency anxiety and appraisal anxiety. No evidence of avoidance behavior was found. These results suggest that the dimensions measured by the SLWAI may not be universal across differing sociocultural populations. This highlights the importance of assessing anxiety in individual populations with consideration to the unique circumstances in which they learn to write in English as a foreign language. By determining unique aspects of writing anxiety in differing populations, EFL instructors may be better able to identify and then target the needs of their students as they work through the process of developing English-language writing skills.